GIFTED LEARNERS’ IDENTIFICATION PROBLEMS - Brandišauskienė, Agnė (Acta Paedagogica Vilnensia, 2007)
The recognition of abilities and creation of favorable conditions for their development is an old and relevant problem. Studies of scientists from all over the world confirm the necessity to consider gifted learners as an important part of the pedagogical process because of their significant aspects. A personal level comes first, as the quality of formation has to meet the needs and inclinations of every learner. It is followed by a social level since the revelation of all learners’ certain abilities should not make a negative impact on the psychological atmosphere of the training process. Thirdly, the potential of giftedness is also of major importance to political and economic levels as that is human resources of every state. The identification process of a gifted child is problematic seeing that the concept of giftedness is rather complicated. It implies different abilities that can show up with mixed intensity in different time and circumstances. A traditional paradigm allows us to regard giftedness as a static phenomenon. That conception is first of all related to intellectual or academic abilities. Discussion of modern concepts of giftedness, however, provides us with a new paradigm defining giftedness as a dynamic phenomenon conditioned by genetic, personal and environmental factors. To recognize gifted children, one can be guided by two criteria: the points of a test and the value of results. The most common identification of gifted children by using tests is currently not so reliable, yet it remains as an objective evaluation. An alternative way to recognize gifted children is by the reference to better achievements and certain behavior characteristic to the children in question. It can reveal a more dynamic view of giftedness, yet the problem of subjectivity is still there.